The win-win classroom : a fresh and positive look at classroom management - Bluestein, Jane (Corwin Press, 2008)
Recognized for defining a nontraditional approach that really works, Jane Bluestein offers educators ways to prevent discipline problems, build student accountability, and end frustrating power struggles with kids of all ages. This research-based guidebook discusses the impact of stress, brain functioning, learning styles, and social and emotional issues on student behavior.--From publisher's description.